2022
DOI: 10.3389/fimmu.2022.802731
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of lncRNA and circRNA Mediated ceRNA Regulatory Networks in Skin Reveals Innate Immunity Differences Between Wild-Type and Yellow Mutant Rainbow Trout (Oncorhynchus mykiss)

Abstract: Fish skin is a vital immune organ that forms the first protective barrier preventing entry of external pathogens. Rainbow trout is an important aquaculture fish species that is farmed worldwide. However, our knowledge of innate immunity differences between wild-type (WR_S) and yellow mutant rainbow trout (YR_S) remains limited. In this study, we performed whole transcriptome analysis of skin from WR_S and YR_S cultured in a natural flowing water pond. A total of 2448 mRNAs, 1630 lncRNAs, 22 circRNAs and 50 miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
(107 reference statements)
1
7
0
Order By: Relevance
“…2, MSTRG.32014.1, and .29012.1 in regulating at least two immune-related genes (IFIH1, DHIRF). Interferon, CD, and HSP genes were also expressed in our study[ 12 ] …”
supporting
confidence: 64%
See 2 more Smart Citations
“…2, MSTRG.32014.1, and .29012.1 in regulating at least two immune-related genes (IFIH1, DHIRF). Interferon, CD, and HSP genes were also expressed in our study[ 12 ] …”
supporting
confidence: 64%
“…Gene Ontology and Databank (KEGG) pathways associated with innate immunity, such as NAD+ADP-ribosyltransferase activity, immune response to bacterial infection, and RIG-I receptor signaling, including NOD-like receptor signaling and phagosomal KEGG pathways, are depicted. In addition, the role of long non-coding RNAs (lncRNAs) MSTRG.11484.2, MSTRG.32014.1, and MSTRG.29012.1 in the regulation of at least three immunerelated genes (IFIH1, DHIRF) was determined [ 12 ] .…”
Section: Q-rt-pcr This Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune-related ceRNAs may regulate the acute heat stress-induced response mainly by the MAPK signaling pathway ( 77 ). In addition, comparing the whole transcriptome of skin in wild-type rainbow trout, a total of 1630 lncRNAs, 50 miRNAs and 2448 mRNAs were differentially expressed in the skin of yellow mutant rainbow trout, which involved numerous key innate immune-related signaling pathways ( 78 ). In the immune-related lncRNA-mediated ceRNA network, the lncRNAs MSTRG.11484.2, MSTRG.32014.1 and MSTRG.29012.1 together with PC-5p-43254_34, PC-3p-28352_70 and bta-miR-11987_L-1R-1_1 ss8TA were identified to regulate at least 3 immune-related genes, interferon-induced helicase C domain-containing protein 1 (ifih1), DEXH (Asp-Glu-X-His) box polypeptide 58 (dhx58) and irf3 ( 78 ).…”
Section: The Regulatory Roles Of the Lncrna-mirna-mrna Axis In Teleos...mentioning
confidence: 99%
“…Recently, ceRNA (circRNA–miRNA–mRNA) has been reported to play an important role in cell proliferation, cell differentiation, ECM synthesis and degradation, immune response, and growth and development [ 16 , 17 , 18 , 19 , 20 ]. Studies have shown that the circ-0005526/miR-142-5p/TCF4, circ-UBE2G1/miR-373/HIF-1α, circ-0000423/miR-27b-3p/MMP-13, and circ-SEC24A/miR-26b-5p/DNMT3A regulatory axis can promote inflammatory factor-induced chondrocytes apoptosis and extracellular matrix degradation [ 18 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%